MUMMIFIED FETUS CO-TWIN TO A LIVE KID IN A GOAT - HEMALATHA, H; MURUGAVEL, K; KANTHARAJ, S; ANTOINE, D; RAJU, M S (The Indian Journal of Animal Reproduction, 2017)
A full-term pregnant two-year-old doe was presented with the history of delivery of a live kid 6 h earlier followed by mild straining without any progress. The vaginal examination revealed a fully dilated cervix with the presence of a fetal mass in the uterus. With mild traction per-vaginally, a mummified fetus was removed. The doe was administered fluid, analgesic and antibiotic parentally apart from intra-uterine pessaries and the doe has resumed normal health.